Internet effectively : - Adams, Tyrone (Pearson/Addison Wesley, 2006)
Internet Effectively is a comprehensive guide to maximizing your online experience. There’s a difference between simply being online and using the Internet effectively. This book provides readers with the theory and easy to follow hands on activities essential for novice Internet users to become proficient users.